Plasmalogens in bacteria, sixty years on - Goldfine, Howard (Frontiers in Molecular Biosciences, 2022)
The presence of plasmalogens in bacteria has been known for 60 years. The recent discovery of two genes encoding reductases that convert diacyl lipids to 1-alk-1’-enyl 2-acyl lipids has confirmed the derivation of plasmalogens from the corresponding diacyl lipids in bacteria. These genes are widely distributed in anaerobic and in some facultatively anaerobic bacteria. These lipids evolved very early in the history of life on earth. Their persistence during eons of evolution suggests that they play a fundamental role in living organism. Their phase behavior and conformation in membranes is discussed.